ASCOT orbit-following simulations of ion cyclotron heating with synthetic fast ion loss diagnostic: a first application to ASDEX Upgrade. (16th July 2021) - Sipilä, Seppo; Varje, Jari; Johnson, Thomas; Bilato, Roberto; Galdón-Quiroga, Joaquín; Snicker, Antti; Kurki-Suonio, Taina; Sanchís, Lucia; Silvagni, Davide; González-Martín, Javier; Upgrade Team, the ASDEX; MST1 Team, the EUROfusion
Abstract: The orbit-following Monte Carlo code ASCOT interfaced with the radiofrequency Monte Carlo library RFOF can simulate radiofrequency heating of ion populations using wave solutions from full-wave solvers such as TORIC. It is applied to the fundamental mode ion cyclotron resonant heating of hydrogen and 2nd harmonic frequency heating of neutral beam injected deuterium in ASDEX Upgrade discharge #33147 to validate the model against fast ion loss detector (FILD) measurements. In addition, for FILD signal simulations requiring enhanced resolution or scanning the effect of various perturbations such as magnetohydrodynamic phenomena near the plasma edge, a two-stage simulation scheme is presented where the fast ion population is first created by a full ASCOT-RFOF ion cyclotron heating simulation, and the resulting distribution is then used as an input to ASCOT's distribution-sampling marker source module for more efficient simulation of the ICRH ion wall load and FILD signal. A satisfactory agreement with the experimentally observed FILD signal is found.